Comparison of Static Balance among Blind, Deaf and Normal Children in Different Conditions - Aidin Vali-Zadeh; Farhad Rezazadeh; Shirin A'ali; Abbas Mostafa-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Sensory systems including proprioceptive, vestibular and visual network play an important role in motor control. Loss of information from each sensory channel can cause body sway on static positions. Materials & Methods: Seventeen blind children (9 girls, 8 boys) and 30 deaf children (14 girls, 16 boys) participated as the sample groups in Ardabil city. Sixteen normal children (30 girls and 30 boys) also selected as the control group. One leg standing and tandem stance tests (reliability=0.87-0.99) in two condition (eyes open and closed) was used for static balance evaluation. One-Way ANOVA and LSD post hoc test was used to compare groups, and independent t-test was used for comparing sexes in each group by using SPSS (16 version) software. Results: results showed there is no significant difference between blind, deaf and normal girls in any of the balance tasks (p>0.05). While the balance function of deaf and normal boys was better than blind boys in all balance tasks except for tandem stance with eyes closed (p=0.507). Blind girls were better than blind boys in all balance tasks (p=0.05, p=0.02, p=0.02). Deaf boys were better than girls with deafness in one leg stance and tandem stance (eyes open) tasks (p=0.04, p=0.02, p=0.04) but there was no significant different between deaf boys and girls in any other tasks (p=0.63, p=0.29, p=0.89). Normal boys have better performance than girls and only in tandem stance (eyes closed) (p=0.21) and one leg stance (left foot eyes open) (p=0.99) there was no significant difference between normal boys and girls. Conclusion: findings showed that static balance in deaf and normal children were better than the blinds. Since persons with blindness are not able to compensate the visual loss for postural stability, they show decreased postural stability in static conditions. Inclusive identifying effective factors on balance and its weakness and problems in appropriate time, attention to this factors in training programs for improving balance in sensory impaired children especially the blinds, through specialists, and attending to their physical activity in school is suggested.